Impact of geographical origin upon the electrical and structural manifestations of the black athlete's heart. (29th August 2018) - Riding, Nathan R; Sharma, Sanjay; McClean, Gavin; Adamuz, Carmen; Watt, Victoria; Wilson, Mathew G
Abstract: Aims: Black athletes demonstrate an increased prevalence of repolarization anomalies and left ventricular hypertrophy compared to their white counterparts. Recent international recommendations for electrocardiogram (ECG) interpretation in athletes now account for some of these observations, but little attention is given to whether the heart of the black athlete is universal, or whether substantial differences exist according to geographic origin. Our aim was to examine the impact of geographical origin upon the electrical—and structural manifestations of the black athlete's heart. Methods and results: A total of 1698 male competitive athletes participating in mixed sports presented at our organization for 12 lead-ECG led pre-participation screening, with 1222 athletes undergoing systematic echocardiography. Black athletes were categorized against United Nations defined geographical regions (North, East, Middle and West Africa, African American/Caribbean, South American, and West Asia) and compared with a cohort of non-black athletes who shared a close geographical boarder with Africa (South European White and Arabic North African). The prevalence of an abnormal ECG suggestive of cardiac pathology significantly varied by geographical origin. Repolarization abnormalities were significantly more common among West (6.4%) and Middle African (8.5%) athletes than East (1.5%) and North Africans (1.2%) ( P  < 0.05). Left ventricular hypertrophy was significantly more common among African-American/Caribbean (9.5%) and West African (5%) athletes than West Asian (0.8%), East African (0%), and North African (0%) athletes ( P  < 0.05). This result remained after accounting for body size. Conclusion: The collective term 'black' should not imply that the hearts of all black athletes are universally comparable. There is considerable variability in the cardiac electrical and structural remodelling response to exercise that appears to be dependent on geographic origin.